Planning to provide clean water in pondok Tahfidz Quran Al Fitrah - Hardi, Surya; Ginting, Elisabeth (Talenta Publisher, 2019)
The need for clean water for human life is a primary need. Humans will not be able to live healthy without clean water, because the human body really needs water, the water content in the human body is not less than 70% of body weight (adults). Water serves to transport minerals, vitamins, proteins and other nutrients throughout the body. Body temperature balance will greatly depend on water, because water is a lubricant of the body's tissues as well as pads of joints, bones, and muscles. Once the importance of water for human survival so that the availability and sustainability of water for living things must be maintained. Islamic boarding schools are religious-based educational facilities whose management is still constrained by funding problems. So the facilities are always in a limited state. As is the case with the Quran Al-Fitrah tahfidz Islamic boarding school, which is located in Namo Rambe, which has difficulty in providing clean water to be drunk at the boarding school. This is what USU's dedication team tried to find a solution for, namely by making a filtering facility for clean water from springs to be made ready for drinking wells to be used by partner communities.